The cookie thief [videorecording (DVD)] (Sesame Workshop, 2016)
A cookie art museum has just opened on Sesame Street. Surrounded by beautiful cookie painting, like "Girl with the cookie earring" and the "Muncha Lisa", Cookie Monster and his friends feel as if they're in a whole new world. But when art suddenly starts to disappear, Cookie Monster quickly becomes a suspect. Can Cookie Monster clear his name? Will they find the missing art in time or will Cookie Monster be banished from the museum forever?